IMPLEMENTASI METODE INTERNET SEHAT PADA JARINGAN KOMPUTER WIRELESS DI MASJID AL AMIN BERBAH - Hariman, Isa; Sholeh, Mohammad; Iswahyudi, Catur (Jurnal Jarkom, 2013)
ABSTRACTÂ The development of computer network technology growing rapidly in line with the needs of the community information service that uses computer networks. The need for the use of the Internet in society based so that all parts of society in Indonesia has knowledge of information technology. The mosque is used as a medium for the spread of the Internet due to the expected future output of the deployment of information technology knowledge will be of good content and useful to society. By using this method as a way to surf the internet sound is good and right that will be implemented into the wireless computer networks in the mosque. Healthy internet methods are implemented on the wireless computer networks using a proxy server that will be implemented some security configuration that is OpenDNS, Squid, IPTables and Dansguardian. From the security configuration is tested one at a time by accessing the content of some categories of negative examples to test the efficacy in blocking sites or negative content from the proxy server before. From the research, the combination of multiple security configurations will be selected based on the advantages and disadvantages that will be used so the proxy server. From the entire configuration will be secure wireless computer networks in the mosque Al Amin Berbah. The implementation of the method on a healthy internet wireless computer network at the mosque will produce a safe way to surf from all negative content. Users can surf the internet without being distracted by negative content.Â Keywords: Healthy Internet, Proxy Server, Mosque.Â